Analysis of Bullet and Ball Collision using Theoretical Approach - Gede Wiratma Jaya; Samsul Bahri (Universitas Islam Negeri (UIN) Mataram, 2022)
Collisions between two objects can be analyzed using the concept of the law of momentum conservation. In the case of a collision between two objects, namely a bullet and a ball, it is necessary to analyze using a theoretical approach. This research aims to analyze the velocity and height after a collision. Newton's law of conservation of momentum and Newton's second law in friction conditions are used as the basis of Calculation analysis using analytical and numerical methods. There are air friction coefficients with variations of 0.1, 0.2, 0.3, 0.4, and 0.5 N.s/m. This type of bullet used a 9 mm calibre with a velocity of 380 m/s. The mass of the bullet and ball is 0.008 kg and 0.3 kg, respectively. The results showed that increasing the air fraction coefficient resulted in lower velocity and height achieved by bullet and ball. The increasing discretization value makes the results of numerical calculations consistent with analytical calculations.